Development and validation of a whole-cell ELISA for serologically diagnosing Helicobacter pylori infection in Brazilian children and adults: a diagnostic accuracy study - Ogata, Silvio Kazuo (2018)
BACKGROUND: Serological tests are practical, with low cost, but no noninvasive tests are available for diagnosing Helicobacter pylori (H. pylori) infection in Brazil. The aim here was to develop and validate en‑ zyme‑linked immunosorbent assay (ELISA) serological tests to detect anti‑H. pylori immunoglobulin G an‑ tibodies, based on cultured strains from Brazilian patients. DESIGN AND SETTING: Cross‑sectional, diagnostic accuracy study comparing a locally developed and validated ELISA and invasive tests among dyspeptic patients at two public hospitals in São Paulo, Brazil. METHODS: An ELISA test was prepared using whole‑cell antigen from 56 strains. After genotypic charac‑ terization, it was standardized and optical density (OD) cutoffs were determined based on the serum an‑ tibody response of 100 H. pylori‑negative samples, compared with 82 H. pylori‑positive samples. Validation was performed on 174 symptomatic patients. RESULTS: The optimal OD cutoffs established (for monoclonal and polyclonal tests, respectively) were 0.167 and 0.164; overall ELISA sensitivity: 84.3%, 78.9%; specificity: 88.6%, 90.6%; positive predictive value (PPV): 75.4%, 80%; negative predictive value (NPV): 93.1%, 81.8%; accuracy: 87.3%, 86.2%; child and ad‑ olescent ELISA sensitivity: 74.2%, 81.8%; specificity: 90.8%, 86.7%; PPV: 66.6%, 84.3%; NPV: 95.8%, 84.8%; accuracy: 88.5%, 84.6; adult ELISA sensitivity: 84.4%, 75%; specificity: 86.9%, 93%; PPV: 81.8%, 78.3%; NPV: 88.9%, 91.8%; accuracy: 85.9%, 88.5%. CONCLUSION: The polyclonal serological test developed using local strains presented better diagnos‑ tic performance among children and adolescents, while the monoclonal test was better among adults. The results from both tests suggest that these in‑house serological tests could be used to detect anti‑H. pylori antibodies in our population, for screening purposes.